Tekutinová resuscitace u stavů s narusenou kapilární permeabilitou - Matĕjovic, M; Novák, I; Rokyta, R; Krouzecký, A (Casopis lekaru ceskych, 2002)
Fluid resuscitation remains a cornerstone in the treatment of various types of circulatory failure. Alterations in microvascular permeability are a hallmark of a number of inflammatory conditions including sepsis, septic shock, burns and the acute respiratory distress syndrome. As a result, the loss of plasma fluid into the interstitial space leads to hypovolaemia and tissue hypoperfusion. Administration of large volumes of fluids in often necessary to restore the nutritional blood flow to tissues. This strategy, however, involves the risk of interstitial edema formation, which in turn may further impair tissue oxygen distribution. The presented paper briefly reviews the principles of transvascular fluid exchange and the pathophysiology of capillary permeability. It discusses the ongoing controversy on the optimal way and the end points of volume replacement as well as the choice of fluid in conditions associated with capillary leakage.
Keywords: Capillary Permeability; Isotonic Solutions; Crystalloid Solutions; náhražky plazmy; syndrom kapilárního úniku; isotonické roztoky; krystaloidní roztoky; lidé; resuscitace; Capillary Leak Syndrome; Fluid Therapy; Resuscitation; tekutinová terapie; Humans; Plasma Substitutes; kapilární permeabilita